INFLUENCE OF HOST STAGE ON OVIPOSITION, DEVELOPMENT, AND SEX RATIO OF Anagyrus lopezi (DE SANTIS) (HYMENOPTERA: ENCYRTIDAE), A PARASITOID OF THE CASSAVA MEALYBUG, Phenacoccus manihoti MATILE-FERRERO 1 (HEMIPTERA: PSEUDOCOCCIDAE) - Adriani, Evie; Rauf, Aunu; Pudjianto, Pudjianto (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2020)
Influence of host stage on oviposition, development, and sex ratio of Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae),a parasitoid of the cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae). The parasitoidAnagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) was introduced from Thailand into Indonesia in early 2014 to controlthe invasive cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae). Because of the need toproduce large numbers of high-quality females, research was conducted in the laboratory to determine host stage preferencefor A. lopezi on different instars of P. manihoti. Individual female wasps were exposed to first, second, third instar nymphs,and pre-reproductive adult mealybugs. In the no-choice test, the frequency of parasitized hosts and the number of eggs laidper host was significantly higher in second and third instar nymphs as well as adult mealybugs compared to first instarnymphs. In the two-choice test, third instars nymphs and adult mealybugs were the most preferred host for oviposition.Immature development of parasitoids was faster and the ratio of female to male parasitoids was higher following ovipositionin second and third instar nymphs and pre-reproductive adult hosts, compared to the first instar nymphs. Our findingsindicate that the use of pre-reproductive adults as hosts in a mass-rearing program would be the most productive and fastestway to produce A. lopezi populations with a female-biased sex ratio. Field release of parasitoids should be conducted whenthe host’s third instar nymph is the most abundant because the period during which preferred and suitable host stages areavailable would be the longest.